Fixed Point Theorems on Soft \(S\)-Metric Spaces - Gunduz Aras, Cigdem; Bayramov, Sadi; Cafarli, Vefa (Communications in Mathematics and Applications, 2018)
The first aim to this paper is to define soft \(S\)-metric spaces and to investigate some important properties. In addition to, we prove some fixed point theorems of soft contractive mappings on soft \(S\)-metric spaces.
Keywords: Soft set; soft \(S\)-metric space; soft contractive mapping; fixed point theorem